Pengaruh Fasilitas Kerja terhadap Kinerja Pegawai Puskesmas Rawat Inap Merlung Kabupaten Tanjung Jabung Barat - Reni Devita; Muhammad Emil; Rasdi Rasdi; Wahyudi Wahyudi (Universitas Batanghari Jambi, 2023)
The purpose of this study was to identify and describe work facilities and the performance of Merlung Inpatient Health Center staff, to identify and analyze the effect of facility work on the performance of Merlung Inpatient Health Center staff. The benefit of this research is to provide additional information for interested parties in the industrial world about work facilities related to employee performance so that efforts can be made to maintain work facilities that can improve work for employees. This research is a descriptive research to test the hypothesis, the sample of this research is the Merlung Inpatient Health Center staff as many as 33 people, using the population census method as respondents in answering the statements. Data collection techniques using statements. The data analysis technique used is SPSS with simple regression analysis and t test. The research method uses descriptive and quantitative analysis methods with library research, research fields, and questionnaires. The location of this company is on Jl. Bhakti Husada, Merlung, Kec. Merlung, West Tanjung Jabung Regency, Jambi 36552, Indonesia. The result of calculating the t-count value is 3,063 using the SPSS program while the t table is 2,039 with a significant level of 5%, df (31) from the t table distribution. Shows that the t-count value is greater than t-table (t-count > t-table) = 3.063 > 2.039. This shows that work facilities affect the performance of Merlung Inpatient Health Center employees. Based on the results of calculations using SPSS it shows that work facilities affect the performance of Merlung Inpatient Health Center employees seen from the value of the coefficient of determination with a value of 0.232 or 23.2% while the rest 76.7% by other variables not explained in this lesson. This shows that work facilities affect the performance of Merlung Inpatient Health Center Employee Performance. It is hoped that the Merlung Inpatient Health Center will pay attention to inadequate or incomplete facilities to support employee work processes and have an impact on work results.